Longitudinal Associations of Phthalate Exposures During Childhood and Body Size Measurements in Young Girls. Issue 4 (July 2016) - Deierlein, Andrea L.; Wolff, Mary S.; Pajak, Ashley; Pinney, Susan M.; Windham, Gayle C.; Galvez, Maida P.; Silva, Manori J.; Calafat, Antonia M.; Kushi, Lawrence H.; Biro, Frank M.; Teitelbaum, Susan L.
Abstract : Background: Phthalates are environmental chemicals that may play a role in the development of obesity. Few studies have investigated longitudinal associations between postnatal phthalate exposures and subsequent anthropometric measurements in children. Methods: We collected data as part of The Breast Cancer and Environment Research Program at three US sites. A total of 1, 239 girls, aged 6–8 years, were enrolled in 2004–2007. We categorized baseline phthalate exposures, assessed from creatinine-corrected urinary concentrations of low-molecular weight phthalate metabolites, as low, <78; medium, 78 to <194; and high, ≥194 μg/g creatinine and of high-molecular weight phthalates as low, <111; medium, 111–278; and high, ≥278 μg/g creatinine. Anthropometric measurements were collected through 2012 (n = 1, 017). Linear mixed effects regression estimated how baseline low and high-molecular weight phthalate concentrations related to changes in girls' body mass index (BMI), height, and waist circumference at ages 7–13 years. Results: Low-molecular weight phthalates were positively associated with gains in BMI and waist circumference. Predicted differences in BMI and waist circumference between girls with high versus low concentrations of low-molecular weight phthalates increased from 0.56 (95% confidence interval [CI]: −0.02, 1.1) to 1.2 kg/m 2 (95% CI: 0.28, 2.1) and from 1.5 (95% CI: −0.38, 3.3) to 3.9 cm (95% CI: 1.3, 6.5), respectively. High-molecular weight phthalates were negatively associated with height but only among girls who were normal weight at baseline (BMI ⩽ 85th percentile). Conclusion: Phthalates, specifically low-molecular weight phthalates, have small but detectable associations with girls' anthropometric outcomes. Low-molecular weight phthalates showed stronger associations than other types of phthalates. Abstract : Supplemental Digital Content is available in the text.